Symbolic Study- Representation in Nyongsong Dance - Widyanarto Widyanarto; Febrianti Febrianti; Mega Lestari Silalahi (Jurnal Seni Tari, 2023)
Nyongsong dance tells of the activities of clove harvesting farmers in the Anambas Islands. Harvesting cloves includes climbing, picking, crushing, and drying cloves. This research is qualitative. The data collection technique was carried out by researchers through participatory observation, and the data analysis stage used qualitative descriptive methods. The presentation of the Nyongsong dance consists of three rounds, act 1 presents the farmers climbing and picking cloves symbolized by up and down movements exploring the clove tree setprop, act 2 presents the activity of crushing cloves symbolized by female dancers exploring the movement of ukel and exploring the properties of the jute sack by male dancers, and in act 3, the activity of farmers drying cloves is presented, symbolized by seven dancers exploring brown cloth together. This Nyongsong dance used corrective makeup with brown and green clothes. The props used in this dance are inspired by the tools farmers use when harvesting cloves, such as bags, winnowing, and burlap sacks. Danced by seven dancers, including two male dancers and five female dancers. The accompanying music is created life using Malay musical instruments such as selondang, serunai, violin, mong, gong, bebano, darbuka, flute, multiped percussion, and sequencer. This research aims to examine the Nyongsong dance from the perspective of representational symbols as enriching knowledge about the study of choreography through symbols and representations.